2018
DOI: 10.1080/10253890.2018.1474874
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase and redox status in amygdala, hippocampus and cortex of male Wistar rats in an animal model of post-traumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) is a highly prevalent and impairing disorder. Oxidative stress is implicated in its pathogenesis. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is an important source of free radicals. The aim of the study was to assess oxidative stress parameters, activities of respiratory chain enzymes, and the expression of NADPH oxidase subunits (gp91phox, p22phox, and p67phox) in the single prolonged stress (SPS) animal model of PTSD. Twenty-four (12 controls; 12 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The current study demonstrated that there was a depletion in the non-enzymatic antioxidant GSH concentration in PTSD women when compared to the external healthy control group. These findings are similar to those of Borovac et al and Petrovic et al, who showed GSH depletion in humans with PTSD [42] and in animal rats with PTSD [35]. Our findings suggest that, when OXS persists for an extended period and the body's cellular defense mechanisms cannot effectively combat these processes, the available free GSH decreases, resulting in irreversible cellular degeneration and cell mortality [43].…”
Section: Effect Of Ptsd On Antioxidant Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…The current study demonstrated that there was a depletion in the non-enzymatic antioxidant GSH concentration in PTSD women when compared to the external healthy control group. These findings are similar to those of Borovac et al and Petrovic et al, who showed GSH depletion in humans with PTSD [42] and in animal rats with PTSD [35]. Our findings suggest that, when OXS persists for an extended period and the body's cellular defense mechanisms cannot effectively combat these processes, the available free GSH decreases, resulting in irreversible cellular degeneration and cell mortality [43].…”
Section: Effect Of Ptsd On Antioxidant Parameterssupporting
confidence: 91%
“…The current result is in line with other studies indicating that civilian earthquake survivors and the military population developed PTSD, which was associated with an increase in the level of MDA biomarkers of lipid peroxidation [ 12 , 33 ]. Furthermore, two animal studies have shown an association between PTSD and lipid peroxidation in rats with PTSD, showing elevated levels of MDA in various organ tissues when compared to healthy rats [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional animal studies utilizing a SPS model of PTSD in rats, also reported (i) decreased SOD activity; (ii) increased expression of NOX-2 subunits; (iii) increased MDA and phosphorylated AMPK; (iv) decreased GSH levels in amygdala and hippocampi; (v) elevated IL-6 and IL-1beta levels; (vi) higher expression of iNOS and p-p38 in hippocampi; (vii) higher cyclooxygenase-2 (COX-2) mRNA and protein expression, TNF-α, IL-6, prostaglandin E2 (PGE2), and NO levels; and (viii) cell apoptosis in the hippocampi of stress exposed animals [118][119][120][121]. In an IFS rat model of PTSD, the stress-exposed group showed a significant up-regulation of NOX2 and 8-OH-DG levels and a down-regulation of glutamic acid GAD-67 and parvalbumin in the animals' hippocampi [122].…”
Section: Oxs In Animal Models Of Ptsdmentioning
confidence: 99%
“…Significant decreases in IL-10 and TNF-α expression and increases in the iNOS in microglial isolated from the frontal cortex of the SPS-exposed rats on Day1, but not on Day3 or Day7 ( Cotrone et al, 2021 ). Oxidative stress is present in hippocampus and amygdala but not in cortex on Day7 after the SPS procedure ( Petrovic et al, 2018 ). SPS exposure increased the levels of pro-inflammatory markers and microglia activation in the hippocampus and PFC on Day8 ( Hong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%